KOREAN DRAMAS AS A CATALYST FOR SOUTH KOREAN CULTURAL DIPLOMACY: A DACADE OF INFLUENCE IN INDONESIA (2015-2025) - Sari, Imelda; Filia, Filia, Dr.; rostineu, rostineu -- (International Review of Humanities Studies, 2026)
This research explores the role of Korean dramas (K- dramas) as a catalyst for South Korea’s cultural diplomacy in Indonesia over the decade 2015–2025, emphasizing how major drama releases contribute to strengthening soft- power influence. In early March 2024, Netflix premiered the Korean drama “Queen of Tears,” which quickly rose to the top of the Non- English Global TOP 10 list for the week of March 25–31, recording 93.8 million viewing hours. The drama reached top- 10 rankings in 68 countries, including the United States, Canada, Japan, Australia, and India. This global achievement represents the culmination of a decade- long effort by South Korea to construct the perception and appeal of the Korean Wave (Hallyu), reinforcing its role as a powerful instrument of cultural diplomacy. Hallyu has expanded considerably as a strategic soft- power tool, enabling South Korea to improve international relations while simultaneously driving significant economic gains. The global consumption of Hallyu products increased South Korea’s GDP by 0.2% in 2004, equivalent to approximately 1.87 billion dollars, and continued to rise to 12.3 billion dollars by 2019. This economic impact demonstrates how South Korea’s cultural industries have become central to the nation’s diplomatic and economic strategies. Indonesia plays a key role in this development; according to a 2023 South Korean government survey, Indonesia ranked first among 26 countries in the consumption of Korean cultural content, reaching 35.5%. This high level of engagement reflects the deep cultural connection built through sustained exposure to K- dramas. This study applies both qualitative and quantitative methods to assess how South Korean cultural diplomacy particularly through K- dramas has influenced public perception, cultural affinity, and cross- sector economic impacts in Indonesia. Particular focus is given to “Queen of Tears” and its implications for South Korea’s tourism and beauty industries by late 2024, both from Indonesian audiences and the broader international market. The findings indicate that narrative appeal, emotional depth, and global digital distribution channels have significantly strengthened South Korea’s soft- power presence in Indonesia, contributing to increased cultural exchange and positive bilateral sentiment. Overall, this research concludes that K- dramas represent one of South Korea’s most successful cultural diplomacy instruments over the last decade, shaping cultural preferences and fostering deeper international engagement.